The diet and feeding ecology of Conger conger (L. 1758) in the deep waters of the Eastern Ionian Sea - ANASTASOPOULOU, A.; MYTILINEOU, CH.; LEFKADITOU, E.; KAVADAS, S.; BEKAS, P.; SMITH, C.J.; PAPADOPOULOU, K.N.; CHRISTIDES, G. (Mediterranean Marine Science, 2013)
The diet of the European conger eel Conger conger was investigated for the first time in the Eastern Mediterranean. Fish dominated the European conger eel diet in the deep waters of E. Ionian Sea. All other prey taxa were identified as accidental preys. However, intestine analysis showed that Natantia, Brachyura and Cephalopoda might have a more important contribution in the diet of the species. C. conger exhibited a benthopelagic feeding behavior as it preyed upon both demersal and mesopelagic taxa. The high vacuity index and the low stomach and intestine fullness indicated that the feeding intensity of the species in the deep waters of Eastern Ionian Sea was quite low. C. conger feeding strategy was characterised by specialisation in various resource items. A between-phenotype contribution to niche width was observed for some prey categories. European Conger eel feeding specialisation seemed to be an adaptation to a food-scarce environment, as typified in deep-water habitats